EXPLORING PRODUCT QUALITY ON AUTOMOTIVE CUSTOMER PERCEPTION - Dudung Juhana; Irena Larashati; Imelda Megawati (STMIK Mardira Indonesia, Bandung, 2021)
Departing from the phenomenon of a decline in product sales indicated by customer complaints regarding product quality, the researchers conducted a study to determine what factors shape the quality of automotive products seen from customers' perceptions who have made product purchases. The survey approach carries to answer research questions. Respondents are customers who have made a purchase, while the number of respondents is 104 people. Researchers use factor analysis techniques to determine the factors that shape product quality. The study results indicate that three factors make up the reputation, variety, and prospects. Keywords: Product Quality, Customer Satisfaction.